The Potential Development Strategy of Kassi Village as a Tourism Village Based on Agro-Tourism in Jeneponto Regency, Indonesia - Ab, Ahmad; Annisa Tumbel; Saling; Ab, Ernawati; Hasbi, Andi (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2025)
The people living in the Kassi Village still maintain their customs well and have a reasonably high social value. The agricultural potential of the village is that it is possible to use it as a tourist area without reducing the agricultural activities of the local community. This study aims to determine the potential of Kassi Village as a tourism village and identify strategies for developing agro-tourism-based village potential. The method used in this research is a qualitative approach using descriptive analysis, and a SWOT analysis is carried out to determine the potential development strategy of an area. This study's data collection techniques used interview techniques with informants and field observations. The results showed that Kassi Village, located in the highlands of Jeneponto Regency, has abundant natural resource potential and agricultural and plantation areas. The SWOT analysis results found appropriate strategies to develop Kassi Village into a tourism village based on agro-tourism. These natural resources can be used as tourist attractions based on agro-tourism.